2016
DOI: 10.2147/ott.s114052
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between <em>MGMT</em> promoter methylation and gastric cancer: a meta-analysis

Abstract: A DNA repair enzyme, O6-methylguanine-DNA methyltransferase (MGMT), plays an important role in the development of gastric cancers. However, the role of MGMT promoter methylation in the occurrence of gastric cancer and its relationships with clinicopathologic characteristics has not been fully clarified. Thus, we performed a meta-analysis to evaluate the associations between MGMT promoter methylation and gastric cancer. Electronic databases, including PubMed and Web of Science, were used to systematically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Gene silencing and loss of expression of MGMT, tumor suppressor gene, was reported in various types of cancers including breast cancer, colorectal cancer, nonsmall-cell lung cancer, melanoma, gliomas, and gastric cancer that is not related to gene mutations, deletions, rearrangements, or RNA instability. 37,38 Hypermethylation in specific region of promoter was suggested as one of the possible mechanisms for MGMT gene silencing in various cancers. 10,11 In the case of breast cancer, the earlier studies have estimated the frequency of MGMT promoter methylation between 22% and 32%.…”
Section: Discussionmentioning
confidence: 99%
“…Gene silencing and loss of expression of MGMT, tumor suppressor gene, was reported in various types of cancers including breast cancer, colorectal cancer, nonsmall-cell lung cancer, melanoma, gliomas, and gastric cancer that is not related to gene mutations, deletions, rearrangements, or RNA instability. 37,38 Hypermethylation in specific region of promoter was suggested as one of the possible mechanisms for MGMT gene silencing in various cancers. 10,11 In the case of breast cancer, the earlier studies have estimated the frequency of MGMT promoter methylation between 22% and 32%.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation of MGMT is related to gastric cancer risk, distant metastasis, and lymph node metastasis, which indicates that MGMT promoter methylation may play an important role in gastric cancer development [ 67 ]. Promoter methylation of ASC/TMS1 is associated with poor prognosis of patients with gastric cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sawnhey et al, observed that increased risk of nodal infiltration is associated with MGMT methylation in oral cancer (Sawhney et al, 2012). Additionally, Yu and coworkers demonstrated that MGMT methylation increases the risk of nodal metastases in gastric cancer (Yu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%